Computational Systems Biology of Cancer - Emmanuel Barillot (Chapman and Hall/CRC mathematical & computational biology series., 2013)
Concentrating on the most challenging problems for the molecular biology of cancer, this book provides a systematic overview of the current state of the art in computational systems biology. It presents concepts, algorithmic methods, bioinformatics tools, and biological applications, along with accompanying tables and illustrations. The authors introduce theoretical elements and demonstrate them using practical approaches with real data. Each chapter begins with an overview of a biological or clinical question of importance in cancer research or treatment, followed by a description of the current state of the art of the field and a list of available resources